2015
DOI: 10.1007/s10916-015-0282-7
|View full text |Cite
|
Sign up to set email alerts
|

Interactive 3D-PDF Presentations for the Simulation and Quantification of Extended Endoscopic Endonasal Surgical Approaches

Abstract: A three-dimensional (3D) model of the skull base was reconstructed from the pre- and post-dissection head CT images and embedded in a Portable Document Format (PDF) file, which can be opened by freely available software and used offline. The CT images were segmented using a specific 3D software platform for biomedical data, and the resulting 3D geometrical models of anatomical structures were used for dual purpose: to simulate the extended endoscopic endonasal transsphenoidal approaches and to perform the quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
0
17
0
4
Order By: Relevance
“…In 11 (7.1%) more articles, it was claimed that 3D PDF should be available, but no 3D model could be found [ 58 , 72 - 81 ]. Of the 156 articles with applied 3D PDF technology, 34 (21.8%) [ 40 , 55 - 57 , 61 , 64 , 68 , 82 - 108 ] had the 3D content directly embedded into the PDF of the article, 94 (60.3%) [ 20 , 48 , 59 , 60 , 63 , 66 , 67 , 109 - 195 ] articles provided the 3D content as supplementary material, and 28 (17.9%) [ 4 , 41 , 62 , 196 - 220 ] referred to an external resource. The 34 articles in which the 3D objects were embedded directly into PDF of the main article were published in 25 different journals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 11 (7.1%) more articles, it was claimed that 3D PDF should be available, but no 3D model could be found [ 58 , 72 - 81 ]. Of the 156 articles with applied 3D PDF technology, 34 (21.8%) [ 40 , 55 - 57 , 61 , 64 , 68 , 82 - 108 ] had the 3D content directly embedded into the PDF of the article, 94 (60.3%) [ 20 , 48 , 59 , 60 , 63 , 66 , 67 , 109 - 195 ] articles provided the 3D content as supplementary material, and 28 (17.9%) [ 4 , 41 , 62 , 196 - 220 ] referred to an external resource. The 34 articles in which the 3D objects were embedded directly into PDF of the main article were published in 25 different journals.…”
Section: Resultsmentioning
confidence: 99%
“…Day and colleagues [ 109 ] demonstrated that preoperative 3D modeling of magnetic resonance imaging data of fistula-in-ano can reduce confusion and ambiguity among surgeons when interpreting 3D PDF reports instead of complex textual reports. The benefit of 3D PDF for the simulation of surgical procedures was described by Mavar-Haramija and colleagues [ 4 , 41 ] for endoscopic endonasal interventions. Husch and colleagues [ 192 ] demonstrated how automatically generated 3D PDF reports can be used to visualize and assess the spatial relationships between electrodes and brain structures and to detect misplaced electrodes in a postoperative deep brain stimulation setting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique has great potential for almost every scenario wherein 3D objects should be visualized and exchanged between computers with various operating systems. This format widely utilizes biomedical data for the reconstruction of human anatomy to the advantage of medical students or utilizes clinical characteristics for planning surgery ( 3 , 4 ). Besides providing educational information for patients and medical students, 3D PDF offers a very efficient and convenient way to distribute 3D structures by embedding 3D objects into scientific publications especially in digital publications.…”
Section: Introductionmentioning
confidence: 99%